Detection of Mycobacterium abscessus Complex at the Subspecies Level from Surgical Site Infection at a Tertiary Care Hospital in Bangladesh - Sukanya, Marium; Saha, Mili Rani; Rahman , Tanjila; Rahman, Minhaj Rashidur; Hasan, Md. Rokibul; Barai, Lovely (Bangladesh Journal of Medical Microbiology, 2026)
Background: Mycobacterium abscessus complex (MABC) exhibits the highest degree of antimicrobial resistance among the rapidly growing mycobacteria (RGM). These nontuberculous mycobacteria (NTM) are capable of causing various human diseases including surgical site infections (SSI). MABC consists of 3 subspecies: Mycobacterium abscessus subspecies abscessus (M. abscessus), Mycobacterium abscessus subspecies bolletii (M. bolletii), and Mycobacterium abscessus subspecies massiliense (M. massiliense). Significant differences in antimicrobial susceptibility are observed among these MABC subspecies. Since treatment options for MABC are limited and a combination of drugs is needed for prolong period, it is very important to detect MABC at the subspecies level to ensure appropriate patient management. Objective: This study was conducted to detect and differentiate the three subspecies of MABC. Methodology: This cross-sectional study was conducted in the Department of Microbiology of BIRDEM General Hospital from August 2022 to February 2024. Pus/ wound swabs were collected from 150 patients suffering from surgical site infection (SSI). RGM was detected by microscopy and culture. DNA was extracted from the isolates and utilizing 3 sets of subspecies-specific primers, MABC were detected at the subspecies level using conventional PCR in single as well as multiplex settings. Results: Culture of the 150 pus/wound swab samples revealed growth of RGM in 28 cases (18.67%). Among the 28 RGM isolates, 19 (67.86%) MABC were detected by PCR of which 13 (68.42%) were M. abscessus and 6 (31.58%) were M. massiliense. Conclusion: This subspecies-specific PCR test can be routinely used in laboratories to detect MABC at the subspecies level, aiding the selection of appropriate treatment regimens. Bangladesh Journal of Medical Microbiology, July 2025;19 (2):82-88